Analysis of Selection Criteria and Alternatives to Renewing Membership in Fitness Centers Using an Analytical Hierarchy Process - Sevilmiş Ali; Aydoğan Rukiye; García-Fernández Jerónimo (Sciendo, 2023)
The aim of the study was to determine the most suitable fitness center for members by using the Analytical Hierarchy Process (AHP) method, which identifies the criteria fitness members consider when choosing a fitness center. First, interviews were conducted with 20 fitness center members to determine the criteria. Then, the values obtained from the comparisons between the criteria, made by experts, were analyzed and evaluated using the AHP method. Eight criteria were determined: instructor qualification, interactions, cleaning, price, staff qualification, atmosphere, accessibility, equipment modernity and variety. Then alternatives to fitness centers were defined (low price, middle segment, premium) and a group of five experts was formed, consisting of members of various fitness centers and experts in sports sciences, and academics who conduct customer behavior research in fitness centers. Based on the opinions of experts, three alternatives and eight selection criteria were used in the evaluation. Alternatives are listed based on the findings. In the first phase of the study, weighting of the criteria and consistency calculations were performed, after which each criterion was weighted in relation to every alternative. As a result, the best alternative was calculated. According to the findings, price was determined to be the most important criteria in renewing fitness center membership, while premium fitness centers were determined to be the most important alternative. The research provides suggestions for reducing dropout rates and for the decision to renew memberships in fitness centers (such as flexible pricing, customer interaction, quality, and equipment modernity).